2015
DOI: 10.1093/eurheartj/ehv387
|View full text |Cite
|
Sign up to set email alerts
|

Approach to family screening in arrhythmogenic right ventricular dysplasia/cardiomyopathy

Abstract: One-third of first-degree relatives develop manifest ARVD/C. Siblings have highest risk of disease, even after correcting for age and sex. Fulfilment of TFC independent of family history is superior to conventional TFC for arrhythmic risk stratification of relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 16 publications
2
62
0
Order By: Relevance
“…According to the study by Te Riele et al 31,. one-third of first-degree relatives of ARVC probands could develop ARVC, especially siblings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study by Te Riele et al 31,. one-third of first-degree relatives of ARVC probands could develop ARVC, especially siblings.…”
Section: Resultsmentioning
confidence: 99%
“…one-third of first-degree relatives of ARVC probands could develop ARVC, especially siblings. Therefore, the fulfillment of TFC independent of family history is superior to conventional TFC for arrhythmic risk stratification of relatives31. Several studies have reported on the association of family history with the presence of desmosomal gene mutations, but the results remain contradictory.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that lethal ventricular arrhythmias during the ‘concealed phase’ of ARVC, other than expression of a subcellular arrhythmogenic mechanism, may be the result of the low sensitivity of routine clinical tests such as ECG and echocardiography for detection of early/minor arrhythmogenic phenotypic substrates, such as an isolated epicardial scar of the left ventricle, for which detection requires more sophisticated imaging technology such as contrast-enhanced cardiac magnetic resonance. These data were recently confirmed by the study of Te Riele et al showing that in patients with familial ARVC, development of structural abnormalities always preceded the occurrence of ventricular arrhythmias 50 .…”
Section: Discussionmentioning
confidence: 56%
“…Genetic testing can aid early diagnosis of relatives of a clinically affected individual with a disease causing mutation, and may enable early discharge of gene negative relatives from follow-up 293031. Data from qualitative studies suggest testing does not inflict psychological harm and may alleviate uncertainty 3233.…”
Section: How Are Family Members Evaluated?mentioning
confidence: 99%